104P A novel immunological role of hydrogen sulphide in shaping natural killer cells cytoxicity in breast cancer patients. (15th December 2019) - Youness, R A; Abdelmotaal, A; Gad, M
Abstract: Background: Triple Negative Breast cancer (TNBC) is a complex challenging disease that is not amenable to conventional treatment. Our research group has recently portrayed hydrogen sulphide (H2 S) and its synthesizing enzymes, cystathionine β-synthase (CBS) and cystathionine-γ-lyase (CSE), as potent oncogenic mediators for TNBC progression. Recently, H2 S has been casted as a potential modulator of cancer immune surveillance as well. Yet, the impact of H2 S on the immunological profile of TNBC cells has never been investigated. Natural Killer (NK) cells are the native sentinels of the immune system that plays an indisputable role in TNBC-immune surveillance. TNBC immune suppressive tumour microenvironment is also rate-limiting step when immunotherapeutic approaches are tackled in case of TNBC patients. Thus the main aim of this study is to identify the role of endogenous H2 S on NK cells' activating ligands present on TNBC cells, immune suppressive tumour microenvironment and net effect on NK cells cytotoxicity. Methods: Breast tissues were collected from 80 BC patients. ER, PR, HER-2 and Ki-67 levels were quantified using immunohistochemistry. MDA-MB-231 and MCF7 cells were cultured and transfected with different oligonucleotides. Total RNA was extracted and quantified by qRT-PCR. IFN-γ and TNF-α in cellular supernatant was measured using representative ELISA kits. NK cells were isolated from 30 healthy controls. The cytotoxicity of NK cells was measured using LDH Cytotoxicity Assay. Results: MICA, MICB and ULBP2 were significantly down-regulated in TNBC tissues and cell lines. Knocking down of CBS and CSE using siRNAs resulted in a marked increase in MICA/B and ULBP2 expression in MDA-MB-231 cells. Nonetheless, knocking down of CBS and CSE resulted in a marked induction in IFN-γ production and attenuation of TNF-α levels. Upon co-culturing with healthy NK cells, Knocking down of endogenous H2 S resulted in a marked increase in NK cells cytotoxicity. Conclusion: This study showed that knocking down of CBS and CSE resulted in a improving NK cells cytotoxicity and alleviating tumor-induced immune suppressive microenvironment in TNBC patients. Legal entity responsible for the study: German University in Cairo. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.